Entertaining male clients in an Indonesian karaoke café : a study of accommodation strategies / Anisa Larassati - Larassati, Anisa (2013)
Accommodation strategies are important in service based workplace where the choice of appropriate language plays a significant role for both the service output and customers’ preference or satisfaction. Linguistic research on accommodation strategies in workplace discourse mostly focussed on the importance of accommodative communication styles as an integral part of giving good service to the customers. However, the nature of some services might sometimes compel employees to perform non-accommodative communication styles to the customers. In a gendered workplace where service employees often have to deal with their customers’ misbehaviour such as asking for sexual service or coercing them to drink liquor; non-accommodative communications become evident. This study provides analysis of both accommodative and non-accommodative communication styles used by female Guest Relations Officers (GROs – a euphemism term for paid female companions) in an Indonesian Karaoke Café. Approximately 16 hours recordings of interactions between 5 GROs and their 16 clients during 7 Karaoke Sessions were analysed. The latest work of the Communication Accommodation Theory (CAT) by Giles and Gasiorek (2012) was used as the main framework of this study. Analysis of code-choice, address terms, politeness, refusals and other linguistic aspects are also included within the analysis of CAT. This study also provides a critical discussion of how ‘doing gender’ is related to the notion of communicative accommodation. It was found that both accommodation and non-accommodation strategies occur during the participants’ interaction. Different and asymmetrical code exchanges (Bahasa Indonesia and Javanese) among the participants which indicate divergence strategies were sometimes perceived as accommodative by all the participants. Furthermore, crude forms of Javanese were often used as swear words by the service providers while speaking to their clients. This communication styles were perceived as accommodative instead of rapport threatening. Non-accommodative communication styles occur mostly within discourse management and interpersonal control strategies of CAT where the service providers do not attend to or challenge the clients’ dominance and power. This study also shows that the participants’ communication styles were influenced by the nature of workplace, the requirements of doing gender well in the workplace, as well as the way in which the service providers balance the needs of the stakeholder. Keywords: Communication accommodation theory, accommodation strategies, non-accommodation strategies, gendered workplace, doing gender